Conceptualizing cultural hybridization: a transdisciplinary approach - Stockhammer, Philipp (Springer, 2012)
Questioning hybridity / Philipp W. Stockhammer -- Cultural hybridity: between metaphor and empiricism / Andreas Ackermann -- Circulating objects and the power of hybridization as a localizing strategy / Hans Peter Hahn -- Conceptualizing cultural hybridization in archaeology / Philipp W. Stockhammer -- One world is not enough: the transformative potential of intercultural exchange in prehistoric societies / Joseph Maran -- Adjusting the image: processes of hybridization in visual culture: a perspective from early Christian and Byzantine archaeology / Ute Verstegen -- Transfer of German human resource management practices: replication, localization, hybridization / Torsten M. Kühlmann -- From comparative politics to cultural flow: the hybrid state, and resilience of the political system in India / Subrata K. Mitra -- Hybridization in language / Christina Sanchez-Stockhammer -- New Zealand English: a history of hybridization / Daniela Wawra -- From myths and symbols to culture as text: hybridity, literature and American studies / Carsten Schinko -- The agony of the signified: towards a usage-based theory of meaning and society / Remigius Bunia
Literaturangaben
Workshop proceedings. - Includes bibliographical references
Keywords: Geschichte; Konferenzschrift -- 2009 -- Heidelberg; Kreolisierung; Kulturübertragung; Interkulturalität